“Rape victims” versus “rape survivors”: oppression and resistance in individuals’ perceptions of women who have been raped - Hockett, Jericho M. (Kansas State University, 2013)
An overview discusses rape in terms of two systems of social power: oppression and resistance. Components of these systems—i.e., individuals’ rape-related attitudes, beliefs, perceptions, and behaviors, and outcomes—are compared in the literatures on “rape victims” and “rape survivors” (Hockett & Saucier, under review), suggesting that different results and conclusions are associated with different labels applied to the same group (i.e., women who have been raped). Three studies assessed differences in individuals’ rape-related perceptions (Study 1), intergroup helping intentions (Study 2), and interpersonal helping intentions (Study 3) for “rape victims,” “rape survivors,” and “women who have been raped.” Extending feminist and social psychological theories of social power, results generally supported my hypotheses that such labels would produce different perceptions and helping intentions. The discussion addresses implications for theory, limitations, and directions for future research.
Keywords: Rape; Power; Language; Perceptions; Attitudes; Labels; Language, Linguistics (0290); Psychology (0621); Women's Studies (0453)